Bioprocessing technology for production of biopharmaceuticals and bioproducts - Komives, Claire; Zhou, Weichang, 1963- (Hoboken, NJ : John Wiley & Sons, Inc., 2019)
'Written for industrial and academic researchers and development scientists in the life sciences industry, Bioprocessing Technology for Production of Biopharmaceuticals and Bioproducts is a guide to the tools, approaches, and useful developments in bioprocessing. This important guide: Summarizes state-of-the-art bioprocessing methods and reviews applications in life science industries Includes illustrative case studies that review six milestone bio-products Discusses a wide selection of host strain types and disruptive bioprocess technologies'--Provided by publisher.
Part II BioreactorsChapter 4 Bioreactors for Stem Cell and Mammalian Cell Cultivation; 4.1 Overview of (Mammalian and Stem) Cell Culture Engineering; 4.1.1 Cell Products for Therapeutics; 4.1.2 Cell as a Product: Stem Cells; 4.2 Bioprocess Characterization; 4.2.1 Cell Cultivation Methods; 4.2.2 Cell Metabolism; 4.2.3 Culture Medium Design; 4.2.4 Culture Parameters; 4.2.5 Culture Modes; 4.3 Cell Culture Systems; 4.3.1 Static Culture Systems; 4.3.2 Roller Bottles; 4.3.3 Spinner Flask; 4.3.4 Airlift Bioreactor; 4.3.5 Fixed/Fluidized-Bed Bioreactor; 4.3.6 Wave Bioreactor
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Keywords: MEDICAL / Pharmacology; Pharmaceutical biotechnology industry; Biotechnological process monitoring; Biotechnological process monitoring; Pharmaceutical biotechnology industry; Biological Products -- chemistry; Drug Compounding; Technology, Pharmaceutical; Bioreactors; Electronic books